A CASE REPORT ON TRAUMATIC DELAYED EPIDURAL HEMATOMA WITH ATYPICAL PRESENTATION - Živković, Slavko (Acta medicae Medianae, 2022)
Vertex epidural hematoma (EDH) is an uncommon type of EDH. The management of vertex EDH is a challenge for neurosurgeons, as there is no proper consensus on the proper treatment modality. Our patient had delayed clinical deterioration with the development of paraparesis and deep somnolent state. After an immediate head CT was performed, which showed massive delayed EDH at the vertex, the patient underwent an urgent operation. The postoperative course went satisfactorily with the complete withdrawal of all neurological deficits and control head CT scan showed the complete evacuation of the hematoma. Vertex EDH represents an urgent neurosurgical pathology, which should not be diagnostically overlooked, and by need treated urgently in the operating room.
Keywords: epidural hematoma, superior sagittal sinus, trauma, dural tenting suture, epidural hemostasis